Web-based correspondence management information system at BPKAD Magelang City - Astuti, Dwi; Sutiyatno, Sukris; Kusuma, Ahmad Fauzi Anggi Ariesta (International Journal of Computer and Information System (IJCIS), 2024)
This study aims to design a Mail Management Information System to become more organized. The research procedure used is the development of the Waterfall engineering method from Sommerville with stages including requirements definition, system and software design, unit implementation and testing, system integration and testing, operation and maintenance. The design used in this study is Data Flow Diagram while database design uses Entity Relationship Diagram (ERD). The result of BPKAD Magelang City this research is that a Mail Management Information System has been built at BPKAD Magelang City which can facilitate the process of recording and searching and save storage space